2013
DOI: 10.1128/aem.03755-12
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Determination of Clostridium Endospore Membrane Fluidity during Pressure-Assisted Thermal Processing in Combination with Nisin or Reutericyclin

Abstract: bThis study determined the membrane fluidity of clostridial endospores during treatment with heat and pressure with nisin or reutericyclin. Heating (90°C) reduced laurdan (6-dodecanoyl-2-dimethylaminonaphthalene) general polarization, corresponding to membrane fluidization. Pressure (200 MPa) stabilized membrane order. Reutericyclin and nisin exhibit divergent effects on heat-and pressure-induced spore inactivation and membrane fluidity. P ressure-assisted thermal sterilization (PATS) of food is an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Spores were also germinated by a higher pressure of 550 MPa. This treatment is thought to directly induce Ca 2ϩ -DPA release via Ca 2ϩ -DPA channels (16,18,19) and/or to induce a phase shift of the inner spore membrane (40)(41)(42). Again, it could be shown that germinations induced by 550 MPa were inhibited by NaCl: increasing NaCl concentrations clearly decreased the amount of DPA released, with 3.6 M NaCl no longer allowing any detectable DPA release (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Spores were also germinated by a higher pressure of 550 MPa. This treatment is thought to directly induce Ca 2ϩ -DPA release via Ca 2ϩ -DPA channels (16,18,19) and/or to induce a phase shift of the inner spore membrane (40)(41)(42). Again, it could be shown that germinations induced by 550 MPa were inhibited by NaCl: increasing NaCl concentrations clearly decreased the amount of DPA released, with 3.6 M NaCl no longer allowing any detectable DPA release (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, the germination triggered by 550 MPa was also inhibited by NaCl. As treatments with a 550-MPa pressure directly induce Ca 2ϩ -DPA release, likely by activation of SpoVA channels and/or a phase shift of the inner spore membrane (16,18,19,(40)(41)(42), NaCl probably does not inhibit germination at the levels of signal integration and transduction from the germinosome.…”
Section: Discussionmentioning
confidence: 99%
“…A pressure of 400 to 800 MPa at ambient temperature triggers release of Ca-DPA to induce germination independent of nutrient receptors (6,7). Treatment at 600 MPa and 80°C or higher inactivates spores without triggering physiological processes involved in spore germination (6,8,19,41). Previous studies hypothesized that the insertion of spoVA 2mob operon into B. subtilis 168 resulted in higher DPA concentrations in spores and consequently a high-level heat resistance (13,16).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of spores to pressure-assisted thermal sterilization may depend on the spores' ability to retain DPA and on the heat resistance of the DPA-free spores (6,11). The likely mechanisms for spore inactivation at more than 600 MPa and more than 80°C are a compromised inner spore membrane and the inactivation of integral membrane proteins (17)(18)(19). This therefore facilitates Ca-DPA release in the absence of physiological activity (6,20).…”
mentioning
confidence: 99%
“…Although the mechanism of spore killing is unclear, disruption of inner membrane of endospores during PATP might rehydrate the core and allows inactivation of endospores by antimicrobials (Melly et al, 2002). A treatment of clostridial endospores at 600 MPa and 90 • C for 8 min reduced viable spore counts by more than 3 log cycle and resulted in the release of more than 95% DPA but did not affect the membrane fluidity (Hofstetter et al, 2013). Also, antimicrobial substances (nisin and reutericyclin) had a divergent effect on endospore membrane structure during thermal and pressure assisted thermal processing.…”
Section: 2mentioning
confidence: 97%